Pengembangan Algoritma Advanced Encryption Standard pada Sistem Keamanan SMS Berbasis Android Menggunakan Algoritma Vigenere - Sugiyanto Sugiyanto; Rinci Kembang Hapsari (Ultimatics : Jurnal Teknik Informatika, 2016)
Short Message Service (SMS) is working on a wireless network that allows the theft of the message contents. There are risks that could threaten the security of the contents of the message on SMS services, including SMS snooping, and SMS interception. Therefore, it takes security system messages on SMS services to maintain the security and integrity of the message content to cover the security messages. Algorithms Advanced Encryption Standard (AES) using a structure SPN (Substitution Permutation Network) structure, which has the disadvantage of encryption and decryption, so the safety level is low. To cover the security hole of these weaknesses, the researchers conducted the improvement of Advanced Encryption Standard (AES) algorithm security system based on android SMS using Vigenere algorithm, so that the level of security and integrity of the content of the short message becomes higher and difficult to solve. The results showed an average increase in percentage value of the avalanche effect from 37.24% to 42.96%. Keywords—Advanced Encryption Standard, android, message security, encryption.